2013
DOI: 10.1038/ng.2533
|View full text |Cite
|
Sign up to set email alerts
|

The nexin-dynein regulatory complex subunit DRC1 is essential for motile cilia function in algae and humans

Abstract: Summary Primary ciliary dyskinesia (PCD) is characterized by dysfunction in respiratory and reproductive cilia/flagella and random determination of visceral asymmetry. Here, we identify the DRC1 subunit of the Nexin-Dynein Regulatory Complex (N-DRC), an axonemal structure critical for regulation of the dynein motors, and demonstrate that DRC1/CCDC164 mutations are involved in the pathogenesis of PCD. Loss-of-function DRC1/CCDC164 mutations result in severe defects in assembly of the N-DRC structure and defecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
191
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(215 citation statements)
references
References 39 publications
21
191
2
1
Order By: Relevance
“…Although DRC4 is required for proper assembly of the nexin link and its subunits (DRC3 and DRC5-7), DRC4 does not seem to be required for proper assembly of DRC1 and DRC2 into the base plate, as seen by the remaining base plate density in the pf2 mutant. In contrast, DRC1 and DRC2 seem to be important for DRC4 assembly into the N-DRC, because DRC4 is reduced and more easily extracted in the Chlamydomonas DRC1 null mutant pf3 (6,11) and is markedly reduced in the DRC2 (CCDC65) mutant human patient (10). Both DRC1 and DRC2 are missing in pf3, and no base plate density was detected by previous cryo-ET studies (14).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although DRC4 is required for proper assembly of the nexin link and its subunits (DRC3 and DRC5-7), DRC4 does not seem to be required for proper assembly of DRC1 and DRC2 into the base plate, as seen by the remaining base plate density in the pf2 mutant. In contrast, DRC1 and DRC2 seem to be important for DRC4 assembly into the N-DRC, because DRC4 is reduced and more easily extracted in the Chlamydomonas DRC1 null mutant pf3 (6,11) and is markedly reduced in the DRC2 (CCDC65) mutant human patient (10). Both DRC1 and DRC2 are missing in pf3, and no base plate density was detected by previous cryo-ET studies (14).…”
Section: Discussionmentioning
confidence: 85%
“…7). Previous studies reported that DRC4 can bind to microtubules through its microtubulebinding domain and, in addition, interacts with other N-DRC subunits, such as DRC1 and DRC2 (7,11). Even a mutated DRC4 lacking amino acids 96 -151 (sup-pf3 strain) still binds to microtubules (7).…”
Section: Discussionmentioning
confidence: 99%
“…This complex interconnects the A tubule with the adjacent microtubule pair's B to prevent sliding between tubules from the forces generated by axonemal dynein (35). Several mutants in the nexin complex disrupt the coordinated movement of the axoneme, leading to irregular flagella beating (7,23,32,36,37).…”
Section: Resultsmentioning
confidence: 99%
“…For example, defects of nexin link components [63], central pair components [64], ciliary biogenesis defects [14] and defects caused by DNAH11 [65,66], usually cannot be visualized by classic TEM. Thus, normal ultrastructure cannot rule out PCD.…”
Section: Page 5 Of 36mentioning
confidence: 99%
“…Mutations in CCDC39 [82,83], CCDC40 [82,84], CCDC65 [85] and CCDC164 [63] Numerous proteins are involved in cytoplasmic biogenesis of cilia. The identification of genes involved in cytoplasmic assembly of cilia (HEATR2, DNAAF1, DNAAF2, DNAAF3, DYX1C1, CCDC103, LRRC6, ZMYND10, SPAG1, ARMC4 and C21orf59) has provided clear insights into this process [81,[85][86][87][88][89][90][91][92][93][94][95].…”
Section: Genetics: Pcd Is Generally An Autosomal Recessive Disease Tmentioning
confidence: 99%